Evaluation of The Effectiveness of The Handling Time of Election Violations Election by Gakkumdu - Suleman, Fahmi; Moonti, Roy Marthen; Ahmad, Ibrahim (International Journal of Sociology and Law, 2025)
General Election (Pemilu) is a fundamental pillar of democracy that often faces various challenges, including legal violations that undermine its integrity. To overcome this, the Integrated Law Enforcement Center (Gakkumdu) was formed as a collaboration between Bawaslu, the Police, and the Attorney General's Office to accelerate the handling of election violations. However, the strict handling time limit of 14 working days is a major challenge in achieving fair and effective decisions. This study aims to evaluate the effectiveness of the handling time of election violations by Gakkumdu and identify the inhibiting factors. Using a descriptive-analytical qualitative method, this study found that the main obstacles include inter-agency coordination, sectoral ego, limited human resources, and lack of supporting technology. In addition, differences in legal interpretation and low public legal awareness also slowed down the enforcement process. In conclusion, the effectiveness of Gakkumdu handling time is not optimal and requires policy reform. Recommendations include simplifying procedures, cross-agency training, utilizing technology, and educating the public. These reforms are expected to improve election integrity and support a fairer democracy.